Novel Natural Deep Eutectic Solvent (NaDES) Yellow Choline Chloride and Molecular Docking Soybean Extract (Glycine max) as Diabetes Drugs Candidate - Yulion, Rizky; Aliyah, Siti Hamidatul; Perawati, Santi; Andriani, Lili; Eryunita, Putri; Arfiah, Besek; Atmaja, Anggito Surya (Indonesian Scholar Society, 2024)
Natural Deep Eutectic Solvent (NaDES) is an environmentally friendly extraction method to obtain soybean bioactive compounds, focusing on genistein compounds as drug candidates. The use of environmentally friendly extraction solvents could support green extraction to ensure the safety of natural medicinal candidates. HBA (Hydrogen Bonding Acceptor), yellow choline chloride (supplement in animal feed), and HBD (Hydrogen Bonding Donor) lactic acid. A UV-Vis spectrophotometer was used to detect genistein. MoE 2022.02 software was used in the molecular docking simulation, and the docking scoring methods affinity ΔG and GBVI/WSA (induced fit) were used. The PDB ID used was: 5nn8 (alpha glucosidase) and PDB ID: 7vsi (SGLT-2 Inhibitor). The results of genistein were obtained by 92,670 mg (0.9267%) in the 75 0C, 30 min ultrasonic NaDES extraction in HBD lactic acid. Genistein exhibited an affinity for the 5NN8 (alpha-glucosidase) and 7VSI (SGLT-2 Inhibitor) receptors of -6,230 and -8,768, respectively. These affinity values did not exceed the interaction values of the native ligands acarbose (alpha-glucosidase) and Empagliflozin (SGLT-2 Inhibitor), which were -8,988 and -12,302, respectively. Genistein compounds had the lowest RMSD value of 0.819 at 7vsi (SGLT-2 Inhibitor). These results suggested the possibility of a genistein pathway as a candicate diabetes drug. The NaDES extraction method demonstrated great potential for development into a green action that supported the green extraction process, and genistein was an isoflavone compound that could be a candidate for diabetes drugs.